2005
DOI: 10.1084/jem.20042041
|View full text |Cite
|
Sign up to set email alerts
|

Induction of vascular leakage through release of bradykinin and a novel kinin by cysteine proteinases from Staphylococcus aureus

Abstract: Staphylococcus aureus is a major pathogen of gram-positive septic shock and frequently is associated with consumption of plasma kininogen. We examined the vascular leakage (VL) activity of two cysteine proteinases that are secreted by S. aureus. Proteolytically active staphopain A (ScpA) induced VL in a bradykinin (BK) B2-receptor–dependent manner in guinea pig skin. This effect was augmented by staphopain B (SspB), which, by itself, had no VL activity. ScpA also produced VL activity from human plasma, apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 30 publications
1
94
0
Order By: Relevance
“…The fact that ASP generated VL activity from both kininogens (Fig. 6) is in agreement with the kininreleasing ability of these proteinases (23,42,43), with the exception of subtilisin, a serine protease, that releases kinin only from LK (43). ASP produced more VL activity from kininogens than ScpA, the protease that generates kinin most efficiently of these four listed enzymes (Fig.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The fact that ASP generated VL activity from both kininogens (Fig. 6) is in agreement with the kininreleasing ability of these proteinases (23,42,43), with the exception of subtilisin, a serine protease, that releases kinin only from LK (43). ASP produced more VL activity from kininogens than ScpA, the protease that generates kinin most efficiently of these four listed enzymes (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…We have shown that bacterial proteinases induce VL through activation of the plasma kallikrein/kinin system, and/or direct kinin release from HK and low m.w. kininogen (LK), which represents another kinin source in plasma (21)(22)(23). A. sobria is predominantly isolated in patient's blood (24), and is more pathogenic than A. hydrophila (25).…”
Section: Induction Of Vascular Leakage and Blood Pressure Lowering Thmentioning
confidence: 99%
“…Moreover, several species of oral streptococci produce extracellular proteinases capable of degrading albumin (Lo & Hughes, 1996), immunoglobulin A (Plaut et al, 1974) and salivary proteins (Choih et al, 1979). Many bacteria-derived proteinases cleave human kininogens, resulting in the release of kinins, potent proinflammatory peptides (Herwald et al, 1996;Imamura et al, 2005;Scott et al, 1993; for a review see Imamura et al, 2004). A streptococcal proteinase was also shown to degrade CXC chemokines, thereby blocking the clearance of bacteria from infected tissues (Hidalgo-Grass et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Kinins are vasoactive peptides, which regulate many physiological processes but also act as universal mediators of inflammation (Colman and Schmaier, 1997;Kaplan et al, 2002). Although the increased kinin production at the sites of infection should primarily be thought of as a part of the host defense against invading pathogens (Tapper and Herwald, 2000), some kininexerted effects might be beneficial to pathogens, such as the vascular permeability enhancement which helps them to acquire necessary nutrients or to colonize the host tissues (Miyoshi et al, 2004;Imamura et al, 2005Imamura et al, , 2007. Owing to that dual role, the kinin generation, if moderate and controllable, could be important for maintaining the host-pathogen equilibrium (Frick et al, 2007) but, when excessive, becomes an important pathogenicity factor in severe lifethreatening systemic diseases such as sepsis (Hack and Colman, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Lane 1, kininogen standard samples incubated in the buffer; lane 2, kininogens incubated in YPD medium; lanes 3-7: kininogens incubated with secreted proteinases of: C. albicans (3); C. krusei (4); C. tropicalis (5); C. parapsilosis (6) and C. glabrata (7). Extracellular bacterial proteinases augment the kinin levels at the site of infection through a direct action on the host proteinaceous kinin precursors, the kininogens (Herwald et al, 1996;Maruo et al, 1998;Imamura et al, 2004Imamura et al, , 2005Imamura et al, , 2007 or by a proteolytic activation of zymogen forms of host proteinases of the kinin-forming cascade (Molla et al, 1989;Maruo et al, 1998;Mattsson et al, 2001). Only the latter mechanism has so far been suggested to operate during candidiasis because a purified secreted aspartyl proteinase of C. albicans (Sap) was shown to activate the coagulation factor XII (Kaminishi et al, 1990).…”
Section: Introductionmentioning
confidence: 99%